A comparison of two instructional strategies in developing the reading interests and comprehension of the grade four pupils of WVSU-ILS - Cortez, Antoniette D. (Iloilo City CAS, U.P. in the Visayas, 2008)
This quasi-experimental study sought to compare instructional strategies in developing the reading interests and comprehension of the grade four pupils of the West Visayas State University - Integrated laboratory /school for the acadmic year 2007-2008. A reading interest checklist (RIC) and stanford diagnostic reading test, green llevel, comprehension subtests (forms A and B) were used to gather data for the study. The findings of the study revealed that the reading interest of Class A before the application of the two instructional strategies was interpreted as moderately high and high for class B.Furthermore, the reading comprehension score mean of Class A before the application of the strategies corresponds to Stanine 4 which means average erformance as a group while Class b's comprehension score mean fits in Stanine 3, below average performance as a class. After 10 weeks, there is an increase in the reading interest of Class A from moderately high to high. On the other hand, the reading interest of Class B increased a little but it still belonged to the same bracket as before which was interpreted as high. Both classs' reading comprehension score mean increased. Class A progressed to Stanine 5, average performance and Class B, Stanine 4, average performance.When analyzed inferentially, as an entire group before the application of the two instructional strategies, Class a and B reading interests were not significant statistically. On the contrary, both classes' reading comprehension level was significant statistically. After the application of the treatment, bth classes' reading interest was also not significant statistically.. However, the reading comprehension of both classes was significant and much higher than their pre-test comprehension result after the ten-week implementation of Skill Building Reading and sustained silent Reading. Based on the findings, it can be deduced that Class A's reading interests and comprehension score increased after the ten-week implementation of Skill Building Reading and sustained Silent Reading .
Special Problem (Graduate, Master of Education - English as as Second Language) -- Iloilo City : Division of Professional Education, CAS, University of the Philippines Visayas, March 2008.
Keywords: Reading comprehension -- Grade school pupils -- WVSU-ILS.